60 GHz Ultra-Wideband Impulse Radio Transmitter - Ärlelid, Mats; Wernersson, Lars-Erik; Egard, Mikael; Lind, Erik ; 0000-0001-5432-3479 (9th IEEE International Conference on Ultra-Wideband, Vancouver, Canada, 2009-09-09 - 2009-09-11, 2009)
An impulse radio transmitter at 60 GHz with pulse duration time down to 100 ps is reported. OOK modulation is presented and the results show promise for other modulation schemes. The transmitter consists of a gated tunnel diode in parallel with a coplanar waveguide, which is a design that provides direct conversion from the baseband pulse train to radio frequency wavelets with a center frequency of 60 GHz. This is achieved by turning an oscillator on and off. Pulse repetition rate up to 2 Gpulses/s is measured and the pulse data shows extremely short start up and decay time.
Keywords: Wavelet generator; Impulse radio; Tunnel diode; OOK; Direct conversion